Metacognitive Therapy for Comorbid Anxiety Disorders: A Case Study - Johnson, Sverre U.; Hoffart, Asle (Frontiers in Psychology, 2016)
Abstract We aimed to systematically evaluate a generic model of metacognitive therapy (MCT) with a highly comorbid anxiety disorder patient, that had been treated with diagnosis-specific cognitive-behavioral therapy (CBT) without significant effect. Traditionally, CBT has progressed within a disorder-specific approach, however it has been suggested that this could be less optimal with highly comorbid patients. To address comorbidity, transdiagnostic treatment models have been emerging. This case study used an AB-design with repeated assessments during each therapy session and a 1-year follow-up assessment to evaluate the effectiveness of MCT. Following 8 sessions of MCT, significant decrease in anxiety and depression symptoms, as well as loss of diagnostic status was observed. Outcomes were preserved at 12 months follow up. The generic model of MCT seems promising as an approach to highly comorbid mixed anxiety depression patients. Further testing using more powered methodologies are needed. Keywords: Metacognitive therapy, transdiagnostic, metacognition, anxiety, comorbidity.